Using interactive nonfiction narrative to enhance competence in the informed consent process with 3-year-old children - Mayne, F.; Howitt, C.; Rennie, Leonie (Taylor & Francis, 2017)
© 2017 Informa UK Limited, trading as Taylor & Francis GroupEnsuring young children’s competence to participate meaningfully in the informed consent process is a troublesome ethical issue. Evolving recognition of the influence of context and relationship, researcher perspective, and researcher responsibility to provide adequate support has advanced understanding of how this might be achieved. Here, we report the findings of the pilot trial of a new approach that used an ‘interactive nonfiction narrative’ to enhance young children’s capacity to provide meaningful informed consent. This innovative approach employs (re)telling strategies and technology (interactive) to convey factual information about the research (nonfiction) via a story (narrative) to promote participant understanding. Case studies of two 3-year-old boys and their mothers captured participants’ understanding of the informing and consent process. Data collection in the child’s home took place over 11 weeks and included conversations with children and semi-structured interviews with parents on three occasions, together with videos of children interacting with the informing story. We found that children understood many of the key concepts, including the research problem and how they could ‘help’ (participate). Children also understood that they could cease their participation, with one boy exercising his right to opt out towards the end of the study.